Evaluation of the Physical Condition of NTB Pelatda Athletes for the Kabaddi Sport Branch Towards Pon XXI Aceh North Sumatra in 2024 - Nadirasi, Abdira; Syarifoeddin, Elya Wibawa; Wahyudi, Johan; Syobri, Nazalus; Primayanti, Intan (Jurnal Ilmiah Mandala Education (JIME), 2024)
Physical condition is a prerequisite that an athlete must have in order to improve and develop optimal sporting performance. One of them is the NTB Kabaddi athlete who will compete in the XXI Aceh-North Sumatra PON event in 2024. The problem in this research is what the physical condition of the NTB regional athletes in the Kabaddi sport will be in the 2024 Aceh-North Sumatra PON XXI. The aim is to determine their physical condition. NTB regional athlete in the Kabaddi sport for PON XXI Aceh-North Sumatra in 2024. Physical condition includes Agility, Endurance and Leg Muscle Strength.  This research is a quantitative descriptive study carried out by total sampling on NTB Pelatda Kabaddi athletes, totaling 12 male athletes and 12 female athletes. In the agility test (Illinois Agility Run Test), the average for male athletes was 17.17 in the Fair category, while the female athletes showed an average of 19.14 in the Fair category. The endurance test (MFT or Beep Test) shows that the average endurance test for male athletes is 43.9 in the Poor category, while female athletes have an average of 34.8 in the Poor category. And the leg muscle strength test (Leg Dynamometer) shows that the average score for the leg muscle strength test for male athletes is 229 in the Good category, for female athletes it is 177 in the Good category. From these results, when compared with the previous test, from the results of this evaluation there are still components of physical condition that do not meet the expected criteria, but these results can be used as a benchmark and motivation for athletes to prepare their physical condition better in the future.